2020
DOI: 10.3892/ol.2020.11398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CDK6 regulated by miR‑298 on proliferation and apoptosis of thyroid cancer cells

Abstract: Effects of CDK6 regulated by miR-298 on proliferation and apoptosis of thyroid cancer cells were explored. Seventy-five cases of thyroid carcinoma and adjacent tissues were collected. The expression levels of miR-298 and CDK6 mRNA in tissues and cells were detected by RT-PCR. In addition, thyroid cancer cells and human normal thyroid cells Nthy-ori3-1 were purchased, with the former transfected with miR-298-mimics, miR-298-inhibitor, miR-NC, si-CDK6, si-NC, Sh-CDK6, Sh-NC to build cell models. Then the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…Function and pathway enrichment analysis of the circulating vasculature transcripts in the present study were associated with response to an organic substance, regulation of different cell population proliferation, regulation of gene expression, and mononuclear cell migration, consistent with many previous results [19,20,[91][92][93][94][95].…”
Section: Discussionsupporting
confidence: 92%
“…Function and pathway enrichment analysis of the circulating vasculature transcripts in the present study were associated with response to an organic substance, regulation of different cell population proliferation, regulation of gene expression, and mononuclear cell migration, consistent with many previous results [19,20,[91][92][93][94][95].…”
Section: Discussionsupporting
confidence: 92%
“…Li et al [ 25 ] reported that P27 inhibited CDK6 expression, leading to cell cycle arrest and inhibiting cell proliferation. MiR-298 could target the expression of CDK6 to inhibit the proliferation of thyroid cells and promote the apoptosis of thyroid cancer cells [ 26 ]. Chen et al [ 27 ] found that miRNA-524-5p could negatively regulate CDK6 expression, inhibit osteosarcoma cell proliferation and induce cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%